Postimperialism International Capitalism and Development in the Late Twentieth Century - Becker, David G. (Lynne Rienner Publishers, 2023)
The authors present an original theory of capitalist development that features a power-based, noneconomistic class analysis
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Mai 2023)
Keywords: POLITICAL SCIENCE / Colonialism & Post-Colonialism; Internationale Kapitalbewegung; Wirtschaftsimperialismus; Multinationales Unternehmen; Imperialismus; Entwicklungsländer; Aufsatzsammlung